The probiotic effects of dietary Saccharomyces cerevisiae and Aspergillus niger on the growth and some immunity factors of cultured juvenile beluga sturgeon (Huso huso) - Hasanpour Fattahi, A.; Jafaryan, H.; Khosravi, A.; Abdollahi Arpanahi, D. (2014)
This study was conducted to evaluate the effects of dietary autochthonous Saccharomyces cerevisiae and Aspergillus niger on the growth performance, survival rate, ammonia excretion, immune response and the intestinal microbiota of juvenile beluga sturgeon (Huso huso). Beluga juveniles with average (±SD) weight of 31.8±2.81 g were randomly allocated into 12 oval tanks (1000 l) at a density of 30 fish per tank and triplicate groups and were fed either with a basal control diet (no supplemented with probiotic) or with the basal diet supplemented with S. cerevisiae and A. niger (2×106, 4×106 and 6×106 cells g-1). After 8 weeks of feeding on the experimental diets, growth factors, survival rate, ammonia excretion, immunity parameters and gut microbiota were measured. The results indicated that dietary supplementation of 6×106 (cells g-1) S. cerevisiae and A. niger significantly improved growth indicators, survival rate, immune parameters and ammonia excretion compared to the control treatment. Additionally, total autochthonous intestinal fungus probiotic and Lactobacillus spp. counts were affected by dietary treatment. The results showed that dietary supplementation of S. cerevisiae and A. niger (6×106 cells g-1) had positive effects on growth and immunity factors in cultured juveniles beluga.